2009
DOI: 10.3233/cbm-2009-0564
|View full text |Cite
|
Sign up to set email alerts
|

Associations between HLA-C alleles and papillary thyroid carcinoma

Abstract: Our results revealed certain HLA-C alleles are predisposing factors in papillary thyroid carcinoma in Iranian population. This confirms the previous findings for association between HLA-C alleles and differentiated carcinomas in other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Recent studies also have found associations between HLA-C and Graves'disease, with HLA-C * 07 as predisposing and HLA-C * 03 and HLA-C*16 as protective alleles [26]. We have previously reported an association between HLACw*4 and HLACw*15 allele [18] and papillary thyroid carcinoma in our patients. In this study we have found that the Linkage disequilibrium is strong between HLA-DR and HLA-C loci in our population and HLA-DRB1*04 and HLACw15 were predicted to form a haplotype in our population.…”
Section: Discussionsupporting
confidence: 73%
“…Recent studies also have found associations between HLA-C and Graves'disease, with HLA-C * 07 as predisposing and HLA-C * 03 and HLA-C*16 as protective alleles [26]. We have previously reported an association between HLACw*4 and HLACw*15 allele [18] and papillary thyroid carcinoma in our patients. In this study we have found that the Linkage disequilibrium is strong between HLA-DR and HLA-C loci in our population and HLA-DRB1*04 and HLACw15 were predicted to form a haplotype in our population.…”
Section: Discussionsupporting
confidence: 73%
“…Several case-control studies have examined the association between -31G/C polymorphism and cancer risk (Srivastava et al, 2012), including nasopharyngeal carcinoma (Yang et al, 2009a), esophaseal cancer (Yang et al, 2009b), gastric cancer (Yang et al, 2009a;Borges et al, 2010), hepatocellular carcinoma (Bayram et al, 2011), pancreatic cancer (Theodoropoulos et al, 2010), and urothelial carcinoma (Wang et al, 2009). Immunohistochemical staining for survivin expression in tissue samples of thyroid carcinoma has shown the increased expression of survivin in thyroid carcinoma (Haghpanah et al, 2009). In a study on 110 patients with oral SCC, survivin expression was observed in 82.7% of patients, and all cases with metastatic carcinoma were positive for survivin expression.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its important role in the immune response and high polymorphism, the HLA system is associated with many diseases. Recently, many papers about the association between HLA and many types of tumor have been published, including cervical cancer (Schiff et al, 2005;Madeleine et al, 2008), leukemia (Dorak et al, 2002;Mundhada et al, 2004;Wu et al, 2007;Yari et al, 2008), gastric cancer (Wu et al, 2002;Quintero et al, 2005), ovarian cancer (Kübler et al, 2006), thyroid cancer (Haghpanah et al, 2009), and breast cancer (Cantú de León et al, 2009). …”
Section: Introductionmentioning
confidence: 99%